Many losers – One winner? An examination of vote switching to the AfD in the 2017 German federal election using VAA data - Wurthmann, Lucas Constantin; Marschall, Stefan; Triga, Vasiliki; Manavopoulos, Vasilis (My University, 2020)
The German federal election of 2017 saw significant losses for the two German mainstream parties (Volksparteien) and governing coalition partners, the Christian Democrats (CDU/CSU) and the Social Democrats (SPD). The major beneficiary was the Alternative for Germany (AfD), a right-populist party, which almost tripled its amount of votes received from the 2013 federal election. Making use of data from a Voting Advice Application, this article seeks to explore the AfD’s extraordinary electoral success with particular attention to the party’s capacity to attract voters from the two mainstream and traditionally powerful parties. Drawing on the literature on radical right-wing parties in Europe and tracking the route of AfD from a single-issue Eurosceptic party to a radical party with broader programmatic appeal, this work tests hypotheses regarding demographic, political and attitudinal determinants of voting for AfD, in general, and switching one’s vote to AfD from CDU/CSU or SPD more specifically. In line with previous literature, individual-level analyses show that voting for the AfD seems to be more tangentially related to demographic variables, such as sex, age and education and more strongly connected to political concerns, e.g. “conservative” self-placement and attitudes toward specific policies, immigration and Euroscepticism in particular.
Keywords: 2017 German federal election; AfD; Radical right-wing parties; Volksparteien; Voting Advice Applications